ANALISIS PERILAKU KEUANGAN YANG BERPENGARUH TERHADAP KEPUTUSAN INVESTASI PASAR MODAL - Kartika, Thalia Diva; Pratiwi, Ririh Dian (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2025)
Investment trends in the Indonesian capital market continue to increase. The younger generation has a high interest in the world of investment in the Indonesian capital market. This increase has of course given rise to several new phenomena, one of which is the pump and dump phenomenon. This phenomenon is often referred to as the practice of stock frying carried out by a group of irresponsible people. Many investors have become victims of this illegal practice. Lack of basic investment knowledge causes investors to be trapped in these illegal practices. However, there is a bias in financial behavior that can influence investors in making investment decisions, so this is interesting to discuss. Students who actively carry out transactions in the capital market are the samples for this research. The test used is multiple linear regression.